The Literature of Post-War Displacement: Conflicts over Land for the Construction of the Lenin Steelworks and the Konin Mine - Tomczok, Marta (Porównania, 2025)
The article compares two centers of post-war industry in Poland, Konin and Nowa Huta, by analyzing the process of displacement of landowners designated for the combine, power plant and open-pit mines. The author shows the environmental and psychological aspects of the processes, especially their conflictual course and the role of literature in analyzing the displacement of communities. By referencing the works of Rob Nixon, J.R. McNeill, Peter Engelke, Jacek Wódz and Andrzej Delorme and analyzes the overriding, rhetorical goal of this literature, entangled in creating a convenient forum for visualizing and possibly criticizing the consequences of mass industrial migrations in the Polish People’s Republic.